Kelompok Arisan Berantas Buta Huruf Al Qur'an; Studi Pada Masyarakat Desa Pilobuhuta Kabupaten Gorontalo - Ahmad, Cicin; Mashadi, Mashadi; Mustaqimah, Mustaqimah (TADAYYUN: Journal of Religion, Social and Humanities Studies, 2023)
This paper examines the role of arisan groups in eradicating illiteracy in the Qur'an. This research uses a qualitative approach with field studies. Data were collected by means of observation, interviews, and documentation. The results showed that the arisan group played a major role in eradicating illiteracy in the Qur'an in Pilobuhuta Village. The social gathering was centered at the Nur-Huda Mosque, and received a positive response from the takmirul mosque and the local village government. Opportunity, this social gathering strategy can be a program that can be distributed to other villages to eradicate illiteracy in the Qur'an. The challenges include the availability of appropriate methods in teaching people to read the Qur'an, which vary in age and ability to grasp.